A decision analysis of surveillance for colorectal cancer in ulcerative colitis. Issue 4 (1st April 2000) - Delcò, F; Sonnenberg, A
Abstract : BACKGROUND: Patients with long standing, extensive ulcerative colitis have an increased risk of developing colorectal cancer. AIMS: To assess the feasibility of surveillance colonoscopy in preventing death from colorectal cancer. PATIENTS: A hypothetical cohort of patients with chronic ulcerative colitis. METHODS: The benefits of life years saved were weighted against the costs of biannual colonoscopy and proctocolectomy, and the terminal care of patients dying from colorectal cancer. Two separate Markov processes were modelled to compare the cost-benefit relation in patients with or without surveillance. The cumulative probability of developing colorectal cancer served as a threshold to determine which of the two management strategies is associated with a larger net benefit. RESULTS: If the cumulative probability of colorectal cancer exceeds a threshold value of 27%, surveillance becomes more beneficial than no surveillance. The threshold is only slightly smaller than the actual cumulative cancer rate of 30%. Variations of the assumptions built into the model can raise the threshold above or lower it far below the actual rate. If several of the assumptions are varied jointly, even small changes can lead to extreme threshold values. CONCLUSIONS: It is not possible to prove that frequent colonoscopies scheduled at regular intervals are an effective means to manage the increased risk of colorectal cancer associated with ulcerative colitis.